A painless fracture of a phalanx of the left hand in a patient with type 1 diabetes – case report - Oleszko, Michal; Wąsiewicz, Edward; Fularska, Kamila; Kuźniar, Aleksandra; Szawica, Dominik (Journal of Education, Health and Sport, 2023)
The aim of our study is to present a case report of a patient who, due to advanced symmetrical peripheral diabetic polyneuropathy, was unaware of the fracture of the fifth finger of the left hand and even tried to restore it to its previous position. The 53-year-old patient with type 1 diabetes at the age of 9, who, due to non-compliance with medical recommendations and poor metabolic control (over the last 15 years, HbA1c has never fallen below 8.1%, reaching 11.1% in May 2017), developed complications such as: ischemic heart disease, diabetic retinopathy, nephropathy and peripheral neuropathy. In February 2019, in the morning, when unscrewing the fuel filler cap in the car, the patient suffered a finger fracture. He remained unaware of this fact all day due to the lack of any pain symptoms. It was only in the evening that he noticed the wrong placement of the fifth finger on his left hand. On the next day, there was a slight soreness with pressure, and the swelling deepened, which prompted him to visit the emergency room. An X-ray examination was performed there, which showed a fracture of the shaft of the proximal phalanx of the fifth finger of the left hand with angular setting of the fragments. The finger was immobilized in a plaster cast and the patient was referred for further check-up in a specialist outpatient clinic. Fortunately, the attempt to set the finger on his own did not cause any significant complications, and after removing the plaster cast, the patient regained the use of the broken finger. A recent electromyographic study confirmed the existence of a very advanced peripheral neuropathy. In summary, improperly treated, poorly controlled type 1 diabetes has serious consequences. It is very important that people suffering from it conduct regular self-monitoring of blood glucose levels and lead a healthy lifestyle.